RETROFITTING OF SIMPLE MECHANICAL COMPACTING DEVICE (ROCOS) ON CONVENTIONAL RING SPINNING MACHINE FOR IMPROVING YARN QUALITY - Nasir Uddin; Farhana Afroz; Mohammad Abdul Jalil (European Scientific Journal, ESJ, 2015)
Ring spinning is the most popular and universal spinning system due to its significant advantages in comparison with the new spinning systems. But the yarn properties are hampered in ring spinning system with the increase of spindle speed and spinning triangle. Overall yarn properties can be improved by retrofitting of simple mechanical device (rocos) on conventional ring spinning machine. In this study we try to show, how rocos overcome the negative influences of spinning triangle on yarn quality. It also ensures outstanding yarn properties such as hairiness, strength, imperfections, elongation etc. Inspite of higher spindle speed as compared to the yarns which are produced in conventional ring spinning machine by using same raw materials.